AN ACCOUNTING CURRICULUM. - Saliers, Earl A. (The Accounting Review, 1933)
College of Commerce at Louisiana State University offers a four-year course in accounting. The course can be outlined as follows: Freshman year-elementary accounting, six credit hours; sophomore year-intermediate accounting, six credit hours, junior year-cost accounting, three credit hours; auditing, three semester hours; Senior year-income tax, three semester hours; certified public accountant problems, three semester hours; graduate course in research problems, six semester hours. The organization and contents of these courses are given constant attention with a view to improvement and the meeting of the needs of the students. Essentially, the problem method is employed in all courses, with the possible exception of that given in the freshman year. This is based on the belief, justified by years of experience, that well chosen problems, more than anything else, appeal to the student's imagination and help him to correlate theory with situations that, in so far as possible, typify practical work.